2007
DOI: 10.1016/j.bbrc.2006.11.072
|View full text |Cite
|
Sign up to set email alerts
|

Activity-dependent regulation of BRINP family genes

Abstract: We previously identified a family of novel developmentally regulated genes: BRINP1, 2, and 3, which are predominantly and widely expressed in the CNS from earlier developmental stages to adulthood. In the present study, we investigated the activity-dependent regulation of BRINP expression in the CNS. Among the three BRINP genes, BRINP1-mRNA was specifically up-regulated in the dentate gyrus of mouse hippocampus by kainic acid treatment.In cultured hippocampal neurons, the induction of BRINP1-mRNA was also obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
(26 reference statements)
0
6
0
Order By: Relevance
“…Overexpression of DBCCR-1 suppresses tumour cell growth. Involved in neuronal development (Motomiya et al, 2007) Also referred to as FAM5 family of proteins. EPCS50 EPCS50 EPCS50 expressed in the trophoblast upon implantation of the murine embryo (Hemberger et al, 2000)…”
Section: Sea Anemone Toxinsmentioning
confidence: 99%
“…Overexpression of DBCCR-1 suppresses tumour cell growth. Involved in neuronal development (Motomiya et al, 2007) Also referred to as FAM5 family of proteins. EPCS50 EPCS50 EPCS50 expressed in the trophoblast upon implantation of the murine embryo (Hemberger et al, 2000)…”
Section: Sea Anemone Toxinsmentioning
confidence: 99%
“…Since BRINP1-mRNA was highly expressed in the hippocampus and further up-regulated in the dentate gyrus in an activity-dependent manner [4,6], we examined the course of differentiation of dentate granule neurons in BRINP1-KO to elucidate the biological basis of the abnormal behavior.…”
Section: Resultsmentioning
confidence: 99%
“…Among the three family members, BRINP1 is most widely expressed in various mouse brain regions including hippocampus, and its expression in adult hippocampus is further up-regulated by the increase of neural activity [6]. In addition to the promoted neurogenesis in hippocampus, BRINP1-KO mice showed a set of abnormal behaviors comparable to the symptoms of human psychiatric disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, considering that BRINP2 and BRINP3 are already moderately expressed in the ES‐derived NSCs and that BRINP1 is more extensively and intensively expressed throughout the CNS neurons, the induction of BRINP1 at the stage of neuronal differentiation may be more critical for the cessation of cell cycle progression in terminally differentiated neurons. Additionally, BRINP1 is also induced in an activity‐dependent manner in mature dentate gyrus where neurogenesis continues into adulthood (Eriksson et al, 1998; Motomiya et al, 2007). Furthermore, it has been reported that neurogenesis in adult dentate gyrus is accelerated by neural activity (Bruel‐Jungerman et al, 2007; Ge et al, 2007).…”
Section: Discussionmentioning
confidence: 99%